Prevalência da hipertensão arterial e análise de seus fatores de risco nos núcleos de terceira idade de Presidente Prudente - Converso, Maria Estelita Rojas [UNESP] (2005)
The frequency of the cardiovascular and brainvascular diseases represents an important cause of the reduction of the physical capacity of elderly people, and mortality due to these diseases rises exponentially after 65 years age. The Arterial Hypertension is one of the principal risk factors for cardiovascular diseases. As the disease is asymptomatic, the need to inform the population about the illness is a primordial factor. Based on this statement, the aim of this project was to verify the incidence of the Arterial Hypertension, associating it with the risk factors, in ten Municipal Centers of Senior Citizens of Presidente Prudente. One hundred and fifty senior people were interviewed and their blood pressures were determined. The data show that this population presents incidence of Arterial Hypertension above the expected limits. This fact can be explained by the age group of the studied population and by the high rate of some risk factors, reinforcing the need of orientations and explanations to the population about this illness, the risk factors, and the importance of seeking medical attendance periodically.